1985
DOI: 10.1111/j.1532-5415.1985.tb04185.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of the Cholinergic Deficit in Alzheimer's Disease

Abstract: Two studies investigated the ability of physostigmine, given both intravenously and orally, to reduce symptoms of Alzheimer's disease. Intravenous physostigmine significantly and reliably enhanced memory in 13 of 16 patients tested, but the dose producing the improvement varied among patients. Oral physostigmine decreased overall symptom severity in a reliable way in seven of 12 patients tested. The extent of improvement was correlated with the increase in mean cortisol secretion produced by physostigmine, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…We did not observe a narrow therapeutic window, as described in studies of intravenous physostigmine with SDAT patients (26,27). It is our impression that age may play an important role in defining response to physostigmine.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…We did not observe a narrow therapeutic window, as described in studies of intravenous physostigmine with SDAT patients (26,27). It is our impression that age may play an important role in defining response to physostigmine.…”
Section: Discussionsupporting
confidence: 49%
“…Second, intravenous administration is impractical as a meaningful long-term treatment of memory loss in MS. Future trials may wish to evaluate the effectiveness of oral cholinesterase inhibitors. Oral physostigmine has been studied extensively in patients with SDAT (26)(27)(28)(29)(30)(31)(32)(33) and amnesic patients (34,35). Third, it is unclear from this study if the positive effects observed on the SRT can be extrapolated to the memory demands of everyday living.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Anticholinesterase Physostigmine Yes (Bartus 1979c;Bartus and Dean 1988c) Yes (Agnoli et al 1983;Christie et al 1981;Davis et al 1979;Mohs et al 1985) Anticholinesterase…”
Section: Attempts To Extend the Insight To Help Refine Rodent Modelsmentioning
confidence: 96%
“…This concept has been subsequently supported by the findings of severe degeneration of cholinergic neurons, reduced ACh synthesis and levels, decreased choline levels as well as down-regulated activity of choline acetyltransferase (ChAT), and the deregulations of ACh receptors in AD brains [47, 5561]. Moreover, the concentration of ACh in the cerebrospinal fluid (CSF) extracted from AD patients is significantly reduced, and the levels of CSF ACh are proportionate to the severity of cognitive deficits in AD [6264]. These observations have confirmed the perturbations of cholinergic system in the development of AD and further implicated the possibility of using CSF ACh as a diagnostic biomarker of AD.…”
Section: Synaptic Transmission Changes In Admentioning
confidence: 99%